Postwar Vietnam : dilemmas in socialist development - Marr, David G.; White, Christine Pelzer (Southeast Asia Program series, 1988)
This anthology concentrates on domestic questions, economic policies, and socialist development and ideology. The essays' subjects include such varied topics as education, economics, the military, leadership, and economic assistance and humanitarian aid.